2009
DOI: 10.7322/jhgd.19913
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos usuários de um centro de atenção psicossocial infantojuvenil da grande São Paulo, Brasil

Abstract: Trabalho resultante do processo FAP/ESP nº 2006/06902-2-2, realizado pelo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 7 publications
1
14
0
27
Order By: Relevance
“…Couto (2012), following a metanarrative review of the literature on CAPSi published in Bra-zilian journals between 2002 and 2010, emphasizes that despite the important presence of children and adolescents with ASD in the CAPSi, there is no systematized information on the care offered to them in such facilities. Studies surveying data on the various diagnoses in the CAPSi report a prevalence of developmental disorders (Code F.80, in the 10 th edition of the WHO International Classification of Diseases -ICD 10), which include autism, of around 14.2% (Hoffman;Santos;Mota, 2008), 16.2% (Delfini et al, 2009) and 27.5% (Ronchi;Avellar, 2010). More recently, Lima et al (2014), in research carried out in the Rio de Janeiro metropolitan area to produce quality indicators of care for children and adolescents with ASD in the CAPSi, recorded an important gap related to the absence of assessment studies on community services for autistic children.…”
Section: Introductionmentioning
confidence: 99%
“…Couto (2012), following a metanarrative review of the literature on CAPSi published in Bra-zilian journals between 2002 and 2010, emphasizes that despite the important presence of children and adolescents with ASD in the CAPSi, there is no systematized information on the care offered to them in such facilities. Studies surveying data on the various diagnoses in the CAPSi report a prevalence of developmental disorders (Code F.80, in the 10 th edition of the WHO International Classification of Diseases -ICD 10), which include autism, of around 14.2% (Hoffman;Santos;Mota, 2008), 16.2% (Delfini et al, 2009) and 27.5% (Ronchi;Avellar, 2010). More recently, Lima et al (2014), in research carried out in the Rio de Janeiro metropolitan area to produce quality indicators of care for children and adolescents with ASD in the CAPSi, recorded an important gap related to the absence of assessment studies on community services for autistic children.…”
Section: Introductionmentioning
confidence: 99%
“…Among the male subjects, the most frequent diagnoses were schizophrenia, behavioral syndromes, psychological development disorders and behavioral disorders. In the female group, mood and neurotic disorders were more frequently diagnosed (17)(18)(19)(20) .…”
Section: Resultsmentioning
confidence: 99%
“…Less frequent but potentially more severe are psychoses and food problems. Developmental alterations like autism are also less frequent and start during childhood, enduring into adult age (1,8,18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were conducted at CAPSad (alcohol and drugs) (10)(11)(12)(13) , and one of them focused on the elderly (13) . Two studies were performed at CAPS for children and youngsters (14)(15) , whereas only one was conducted at a CAPS for adults (16) . In this study (17) , female users and those who reported studying and homemaking as their occupation prevailed.…”
Section: Introductionmentioning
confidence: 99%